The Influence Of Islamic Branding On Brand Love Through Brand Trust (Study on Safi Skincare Consumers) - Muhammad Nashirul Haq; Arief Noviarkahman Zagladi (Penerbit Jurnal Indonesia, 2024)
The majority of Indonesia's population being Muslim, people are aware of halal Skincare products. The high awareness of halal Skincare products has a major influence on the interest in purchasing products with an Islamic image. If Islamic Branding in Skincare is good, trust will be formed in the brand and in the end consumers will love the brand. This study aims to determine the effect of Islamic Branding on Brand Love through Brand Trust on Skincare Safi consumers.This research uses a quantitative approach with a descriptive and explanatory design. The endogenous variabel in this study is Brand Love (Y), and the exogeneous variable is Islamic Branding (X), while the mediating variabel is Brand Trust (Z) For sample determination, a purposive sampling technique was used with a total sample of 152 respondents with a population of Safi Skincare Consumers who have purchased their products at least three times and consumers aged between ≥15-50 years. The analysis technique used descriptive statistical analysis and Partial Least Square (PLS ) analysisThe results of this research show that: Islamic Branding has a positive and significant effect on Brand Love, Islamic Branding has a positive and significant effect on Brand Trust, Brand Trust has a positive and significant effect on Brand Love, and Islamic Branding has an indirect effect on Brand Love through Brand Trust